2009
DOI: 10.1007/s00586-009-1208-1
|View full text |Cite
|
Sign up to set email alerts
|

Syringomyelia with irreducible atlantoaxial dislocation, basilar invagination and Chiari I malformation

Abstract: A 27-year-old woman presented with bilateral weakness of her all extremities for 5 years. She had a spastic gait and was unable to ambulate without assistance. Neurologic examination revealed increased deep tendon reflexes and positive pathologic reflexes. Radiographs showed occipitalization of the atlas, C2-C3 congenital fusion and fixed atlantoaxial dislocation with an atlanto-dental interval of 10 mm. MRI demonstrated cervicomedullary junction (CMJ) compression from the odontoid, a Chiari type I malformatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 9 publications
0
19
0
1
Order By: Relevance
“…In addition, Chari malformation [21] and thalassemia minor [22] have also been related to atlas deformities. However, the medical history of the cadaver from which the vertebra was obtained made no mention of those syndromes, thus the anatomical variations would have been caused by a pre-mortem injury or during post-mortem handling of the specimen.…”
Section: Case Reportmentioning
confidence: 97%
“…In addition, Chari malformation [21] and thalassemia minor [22] have also been related to atlas deformities. However, the medical history of the cadaver from which the vertebra was obtained made no mention of those syndromes, thus the anatomical variations would have been caused by a pre-mortem injury or during post-mortem handling of the specimen.…”
Section: Case Reportmentioning
confidence: 97%
“…Dissection of the bilateral longus coli and longus capitis muscles and the anterior longitudinal ligament was performed, followed by partial resection of the C1 anterior arch. 4,8 The alar and apical ligaments were also resected to obtain sufficient release. The release procedure was deemed complete when the C1 anterior arch could be levered up to the tip of the dens to achieve the anatomic reduction of the AAD ( Figure 3).…”
Section: Operative Techniquementioning
confidence: 99%
“…Shen et al 1 also found that patients with occipitalization and congenital C2-3 fusion tended to have greater anterior atlantodens interval values than others. These patients often have cervical myelopathy or concomitant anomalies such as basilar invagination, secondary Chiari I malformation, and syringomyelia 3,4 and need occipitocervical reduction and fixation. In the literature, posterior occiput-C2 fixation using C2 pedicle screws (C2PSs) has been widely reported and shown to be effective.…”
mentioning
confidence: 98%
“…Consequently, if AAD is not treated in a timely and appropriate manner, the displacement may become irreversible [1][2][3][4]. If observation of the dynamic X-ray shows that the reduction of the atlantoaxial joint failed with skeletal traction under general anesthesia, AAD is considered irreducible [5]. To date, available treatments for IAAD are posterior decompression, anterior release via transoral approach followed by posterior xation, and transoral atlantoaxial reduction plate (TARP) internal xation, to name a few [6][7][8].…”
Section: Introductionmentioning
confidence: 99%